RANCANG BANGUN SIMULASI DISPLAY ARUS GANGGUAN RELAI PROTEKSI SEL 551 DI MASTER STATION PADA SCADA SURVALENT SEBAGAI UPAYA MEMPERBAIKI SAIDI - Azhar, Dzulfikar Muhammad; Yuniarto, Yuniarto (Gema Teknologi, 2015)
Dzulfikar Muhammad Azhar, Yuniarto, in this paper explian that disruption of the power distribution network of 20 KV greatly influence the level of reliability of electric power system. Localize interference by means of network down one by one causing a long recovery time. As a result, SAIDI relatively high value. Protection Relays 551 SEL has a feature that can save the nominal fault current value last received. The value stored in the relay memory. Value of fault current can be processed into the distance nuisance. Thus, the fault current value can help officers to track the fault location based on distance. SCADA as a system that monitors and controls the electrical power system equipment remotely in real time on duty to display the current value of disturbance located at 551 SEL protection relays to be sent to the Control Center or the Master Station. Keywords : SCADA, fault current, relay protection 551 SEL